Socioemotional Wealth and Firmsâ Control: Evidence from Malaysian Chinese Owned Companies - Goh, Chin Fei; Rasli, Amran; Tan, Owee Kowang; Choi, Sang Long (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2015)
This paper explores how the preservation of socioemotional wealth can be manifested in the control and corporate governance of Malaysian Chinese firms. Using panel data from the Industrial Products index of the Bursa Malaysia (the Malaysian stock exchange) during 2003-2006, we show that the ingrained âlife-raft valuesâ among overseas Chinese entrepreneurs can be associated with the preservation of their socioemotional wealth, and thus they prioritize control over their firms. Additionally, we confirm the monitoring role of non-dominant large shareholders in reducing the familiesâ influence in managing and enhancing their firmsâ performance. Specifically, control contestability exercised by the non-dominant large shareholders mediates the relationship between a familyâs involvement in management and their firmâs performance.